Sinking fund in high-rise properties: nature, scope and challenges - Mohamad, Nor Asiah; Sufian, Azlinor (INSI Publications, 2014)
Maintenance of strata properties is unique as it requires common contribution from all strata purchasers. The contributions which sometimes referred as charges, levies or fee receive mixed reactions from the purchasers or owners for many various reasons. Some of the issues relate to ignorance on the term „Charges‟ and how the money is used. Sometimes, an owner chooses not to pay to protest against any dissatisfaction over services rendered by the management or their agent. While some may agree to the Charges, others ignore the important of having to pay for future capital expenses. Some of the owners argue that the Charges are sufficient to cover whatever cost required in the maintenance of the building thus additional contribution is not necessary. This paper analyses the laws relating to strata as to how sinking fund is defined and managed in order to provide a basis to regulate sinking fund in Malaysia. This study adopts a qualitative content analysis approach in which legal provisions, case laws and other secondary data are analysed in understanding legal framework and policy on sinking fund. The result shows that there are specific purposes for which sinking fund may be spent or utilized by the developers, Joint Management Body or the Management Corporation (MC). The laws also provide the mode for determining the amount of the contribution, make it compulsory for an account to be opened for the collection as well as making it an offence if the management fails to comply with the laws. It is observed that there are considerable improvements in the newly introduced Strata Management Act 2013. Nevertheless, enhancements are still necessary to create awareness among the strata owners to contribute to sinking fund. No doubt, community living requires cooperation and sense of belonging from all especially the owners of the properties.